THE EFFECT OF ORGANIZATIONAL CULTURE, INTRINSIC MOTIVATION, AND KNOWLEDGE SHARING ON EMPLOYEE PERFORMANCE OF CV GLOBAL PRIMA SIDOARJO - Rahmatika Raya Santoso, Purwaningrum; Sumartik , Sumartik; Abadiyah, Rifdah (Universitas Islam Lamongan, 2025)
In this study, the researcher chose CV. Global Prima Sidoarjo as the object of the study with the aim of finding out Organizational Culture, Intrinsic Motivation, andKnowledge Sharingon Employee Performance at CV. Global Prima Sidoarjo. This study uses quantitative research methods, with the type of data used being primary data (survey). The sampling technique used by researchers is the distribution of questionnaires where the population is 41 employees with direct data collection from respondents. The data collection technique in this study uses a Likert scale, a Likert scale is a tool used to measure attitudes, opinions, and perceptions of individuals or groups of people about social phenomena. Analysis techniquesdata testing using Smart Partial Square (PLS) software version 4.0. With the classical assumption test of validity and reliability, Outer Model and Inner Model. The results of the study indicate that Organizational Culture influences Employee Performance, Intrinsic Motivation influences Employee Performance, and Knowledge Sharing influences Employee Performance at CV. Global Prima Sidoarjo.